The hamster as a model system for the study of influenza vaccines. Issue 608 (June 1976) - Potter, C. W.; Jennings, R.
Abstract : A series of experiments was carried out in hamsters to determine their value as an experimental animal for the study of influenza virus infection and immunization. Hamsters could be infected intranasally with approximately 100 EID50 of unadapted influenza A/Port Chalmers/73 virus; infection produced serum HI antibody and virus was recovered from both nasal washings and from lungs. Inoculation of hamsters with influenza virus or inactivated influenza virus vaccine produced immunity to subsequent homologous virus challenge. Groups of hamsters were inoculated with graded doses of a number of different inactivated influenza vaccines: the serum HI antibody response varied greatly for the different vaccines. For some influenza vaccines, the antibody response of hamsters was promoted by prior heterotypic influenza virus infection, but in primed animals the same, wide variation in serum antibody response to different influenza virus vaccines remained. Using the hamster as an experimental model, 60 i.u. of an inactivated A/England/42/72 vaccine gave protection against challenge virus infection; however, 600 i.u. of surface antigen material, including only haemagglutinin and neuraminidase failed to give protection. Inoculation of hamsters with subunit antigens absorbed to alhydrogel gave immunity to challenge virus infection.